2012
DOI: 10.2166/wst.2012.896
|View full text |Cite
|
Sign up to set email alerts
|

Removal improvement of bacteria (Escherichia coli and enterococci) in maturation ponds using baffles

Abstract: Korba wastewater treatment plant is a conventional activated sludge followed by three maturation ponds (MP1, MP2, MP3) in series acting as a tertiary treatment. The first study of wastewater treatment plants showed that the effluent concentration of Escherichia coli and enterococci at the outlet of the (MP3) varies between 10(3) and 10(4)CFU/100 ml. After the hydrodynamic study conducted by Rhodamine WT which showed short-circuiting in the MP1, two baffles were introduced in the first maturation pond (MP1) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…To the best of our knowledge, this is the first study focused on assessing the microbial quality of remote and rural maturation ponds in Australia using both traditional and molecular methods. Based on microbiological analysis and retention time data in the four ponds studied, we suggest that baffled maturation pond WSP1 operates more effectively for pathogen removal ( Figure 2 ), which is in line with previous studies [ 23 , 24 ]. This was demonstrated by a 3 log removal of E. coli counts in the baffled WSP1.…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, this is the first study focused on assessing the microbial quality of remote and rural maturation ponds in Australia using both traditional and molecular methods. Based on microbiological analysis and retention time data in the four ponds studied, we suggest that baffled maturation pond WSP1 operates more effectively for pathogen removal ( Figure 2 ), which is in line with previous studies [ 23 , 24 ]. This was demonstrated by a 3 log removal of E. coli counts in the baffled WSP1.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that, because of the well-designed baffles, the removal efficiency of Escherichia coli increased from 69% to 82% (20). According to the results of the current study, the average K b20 concentrations of the first ponds of the control system were 0.11 d -1 and increased 41.6%, 54.4%, and 69% in 2-, 3-, and 4-baffle systems, respectively.…”
Section: Discussionsupporting
confidence: 58%
“…Ouali et al studied a wastewater treatment plant the process of which was conventional activated sludge followed by three maturation ponds in a series acting as a tertiary treatment. The results showed that the installation of two baffles in the first maturation pond improved coliform removal efficiency (20). This research studied the effects of number of baffles and fixed media packages on the performance of WSPs in the removal of total coliforms of settled wastewater from Choneibeh wastewater treatment plant in the city of Ahvaz.…”
Section: Introductionmentioning
confidence: 99%